Use of the method of micro-arc plasma oxidation to increase the antifriction properties of the titanium alloy surface - Subbotina, V. V.; Sobol, O. V.; Belozerov, V. V.; Makhatilova, A. I.; Shnayder, V. V. (Сумський державний університет, 2019)
The analysis of possibilities on phase-structural engineering of titanium-based alloys during micro-arc plasma oxidation (MAO) is carried out. The influence of phase-structural states on the tribotechnical properties of the modified surface of the titanium alloy VT3-1 is also considered. It has been established that in order to achieve high functional properties, it is necessary to use electrolytes of complex composition for MAO. The presence in the electrolyte of (NaPO₃)₆ leads to the formation of anatase with a low hardness (about 3 GPa). The formation of crystallites of rutile and aluminum titanate with the use of alkaline-aluminum electrolyte allows to increase hardness significantly (up to 7 GPa). The maximum increase in hardness (up to 12 GPa) is achieved in the coating obtained in alkaline-aluminate-silicate electrolyte. This is due to the formation of crystalline mullite. The friction coefficient of such a material decreases (f ‹ 0.01) and as a result, antifriction properties increase. The results of the work indicate the prospects for using the phase-structural engineering method for MAO-processing to optimize the formation of antifriction coatings on titanium alloys.

У статті проведено аналіз можливостей по фазово-структурній інженерії сплавів на основі титану при мікродуговому плазмовому оксидуванні (МДО). Також розглянуто вплив фазово-структурних станів на триботехнічні властивості модифікованої поверхні титанового сплаву ВТ3-1. Встановлено, що для досягнення високих функціональних властивостей необхідно при МДО використовувати електроліти різного складу. Наявність (NaPO₃)₆ в електроліті призводить до утворення анатазу з невеликою твердістю (близько 3 ГПа). Значно підвищити твердість (до 7 ГПа) сприяє формуванню кристалітів рутилу і титанату алюмінію при використанні лужно-алюмінієвого електроліту. Максимальне збільшення твердості (до 12 ГПа) досягається у покритті, отриманому в лужно-алюмінато-силікатному електроліті. Це відбувається через утворення кристалічного мулліту. Коефіцієнт тертя такого матеріалу знижується (f ‹ 0.01) і в результаті цього підвищуються антифрикційні властивості. Результати роботи свідчать про перспективність використання методу фазово-структурної інженерії при МДО-обробці для оптимізації режимів формування антифрикційних покриттів на титанових сплавах.
Використання методу мікродугового плазмового оксидування для підвищення антифрикційних властивостей поверхні титанового сплаву
Keywords: microstructure; X-ray phase analysis; phase composition; hardness; abrasive wear; титан; мікроструктура; рентгено-фазовий аналіз; фазовий склад; твердість